Modelling Temperature and Strain-Rate Dependence of Recycled Aluminium Alloy AA6061 - Ho, C. S.; Mohd Nor, M. K.; A. Samad, M. S. (International Journal of Integrated Engineering, 2022)
Recycling aluminium is a topic of high interest for numerous researchers to cope with the high demand for usage of its primary sources, and to overcome the environmental issues at the same time. Many recycling approaches, including the optimization of the recycling processes have been explored. However, the behaviour of such recycled material under various strain rates and the temperatures is yet established. This is important before an appropriate application can be identified in real practice. Therefore, the works in this manuscript are conducted to characterize the deformation behaviour of recycled aluminium alloy under the uniaxial tensile test using experimental and numerical approaches. The deformation behaviour of the recycled aluminium alloy produced using hot press forging recycling technique is tested over a range of strain rate (Ã—10-4 â€“ Ã—10-3 s-1) and elevated temperature (100Â°C â€“ 300Â°C), where a mild ductile and elastoplastic behaviour are observed, and further compared with the primary form of AA6061. In addition, finite element (FE) model capable of predicting the non-linear behaviour of such materials using the flow stress model of MAT_098: Simplified Johnson-Cook model of LS-DYNA FE code is developed. The characterisation of this constitutive model is also discussed thoroughly in this paper. The numerical results are validated against the experimental data. A good agreement between the experimental and numerical results are obtained. The outcome of numerical analysis is important to prove a strength model is still relevant to predict the deformation behaviour of such recycle material. Further, it showed that further manufacturing advancement is required on the experimental part since an anisotropic parameters are still unavailable, yet vital for consideration.